Two-staged management for all types of congenital pouch colon - Rajendra K Ghritlaharey; K S Budhwani (Wolters Kluwer Medknow Publications, 2013)
Background: The aim of this study was to review our experience with two-staged management for all types of congenital pouch colon (CPC). Patients and Methods: This retrospective study included CPC cases that were managed with two-staged procedures in the Department of Paediatric Surgery, over a period of 12 years from 1 January 2000 to 31 December 2011. Results: CPC comprised of 13.71% (97 of 707) of all anorectal malformations (ARM) and 28.19% (97 of 344) of high ARM. Eleven CPC cases (all males) were managed with two-staged procedures. Distribution of cases (Narsimha Rao et al.'s classification) into types I, II, III, and IV were 1, 2, 6, and 2, respectively. Initial operative procedures performed were window colostomy (n = 6), colostomy proximal to pouch (n = 4), and ligation of colovesical fistula and end colostomy (n = 1). As definitive procedures, pouch excision with abdomino-perineal pull through (APPT) of colon in eight, and pouch excision with APPT of ileum in three were performed. The mean age at the time of definitive procedures was 15.6 months (ranges from 3 to 53 months) and the mean weight was 7.5 kg (ranges from 4 to 11 kg). Good fecal continence was observed in six and fair in two cases in follow-up periods, while three of our cases lost to follow up. There was no mortality following definitive procedures amongst above 11 cases. Conclusions: Two-staged procedures for all types of CPC can also be performed safely with good results. The most important fact that the definitive procedure is being done without protective stoma and therefore, it avoids stoma closure, stoma-related complications, related cost of stoma closure and hospital stay.